Implementasi Health Belief Model terhadap pelaksanaan vaksinasi untuk penanggulangan pandemi Corona Virus Diseases-19 (Covid-19) pada tenaga kesehatan Kabupaten Nagan Raya - Hardiansyah Hardiansyah; Lukman Hakim; Henny Arwina Bangun (Politeknik Kesehatan Kemenkes Aceh, 2021)
Background: World Health Organization (WHO) has declared Coronavirus Disease 2019 (COVID-19) as a pandemic. Interventions are needed not only in terms of implementing health protocols but also other effective interventions to decrease the transmission of disease through vaccination efforts which are aimed at reducing transmission/transmission of COVID-19, reducing morbidity and mortality due to COVID-19, and achieving group immunity in the community society (herd immunity).Objective: The purpose of this study was to identify the implementation of a health belief model for the implementation of vaccination in the context of overcoming the COVID-19 pandemic in health workers within the Nagan Raya District Health Office.Method: The type of research used a descriptive-analytic approach with a cross-sectional study design with a total sampling method of sampling. The sample in this study was 76 health workers from a population of 76 health workers at the Nagan Raya District Health Office. This study was conducted from March to September 2021. Data analysis used Chi-Square statistical test and Binary Logistic Regression with a significance level of 95%.Results: The results of this study indicate that there is a significant relationship between perceived susceptibility (p = 0.041), perceived benefits (p = 0.047), and cues to action (p = 0.037) with the implementation of vaccination in the context of dealing with the COVID-19 pandemic for health workers. There is no relationship between perceived severity (p = 1,000) and perceived barriers (p = 0,280) with the implementation of vaccination in the context of dealing with the COVID-19 pandemic in health workers.Conclusion: The dimension of the health belief model that is highly dominant related to the implementation of vaccination in the context of dealing with the COVID-19 pandemic in health workers is the perceived susceptibility variable with a value of p= 0.041 and Exp (B) = 5.376.